Characterization of the Internal and External Flow Field of a Semi-Submersible Aquaculture Platform with Multiple Net Cage Configuration - Bo Hu; Jiawen Li; Juncheng Ruan; Jiawei Hao; Ji Huang (Journal of Marine Science and Engineering)
To achieve efficient and sustainable marine aquaculture, STAR-CCM+ was used to simulate the internal and external field characteristics of a semi-submersible aquaculture platform based on a porous media model, focusing on the influence of incoming flow velocity and net solidity ratio. The results indicate that the flow field distribution around the platform exhibits no significant regularity and that low-velocity vortex regions are primarily concentrated near the pillars and nets. After velocity attenuation, the velocity reduction coefficients at the centers of the three cages are 90.26%, 63.65%, and 52.56%, respectively. Furthermore, the velocity attenuation inside the cages is minimally influenced by incoming flow velocity, with a maximum difference of 3.10%. In contrast, differences in net solidity ratio significantly affect velocity attenuation, particularly in downstream regions. The velocity reduction coefficient in the third cage varies by up to 43.25% depending on the net solidity ratio. These findings provide practical insights for the engineering design and application of aquaculture platforms.